Sosialisasi Stunting Sebagai Wujud Menciptakan Generasi Yang Sehat, Cerdas Dan Unggul Di Dusun Nyama - Jekriel Septory; Yulina Tiwery (Jurnal Pengabdian Masyarakat Sains dan Teknologi, 2023)
Stunting outreach activities among the community and mothers in Nyama Hamlet were carried out by KKN students at Pattimura University-PSDKU Southwest Maluku as a form of community service. Socialization activities are one of the activities that aim to provide understanding and knowledge to the community and mothers that the problem of stunting is a very important problem for the health of toddlers and children. This socialization was carried out in the form of lectures and questions and answers, this activity was held on August 20 2022, involving the community and specifically mothers in Nyama Hamlet, lasting 1 hour 30 minutes (11:00 – 01:00 WIT). With the aim of providing enlightenment and understanding to the public about the problem of stunting, the causes of stunting and how to prevent stunting in toddlers and children. This activity, carried out by lecturers and several students as a KKN Team, is expected to build awareness and provide a good perspective on preventing stunting which can start from the family itself and the community's contribution in supporting the government to prevent stunting which affects the next generation of Indonesians. This is deemed necessary to create a healthy, intelligent and superior generation in Nyama Hamlet.